Historical Reconciliation: Hungarian Lessons - Egry, Gábor (Identities: Journal for Politics, Gender and Culture, 2023)
The article surveys attempts of historical reconciliation between Hungary and its neighbours after 1990. As Hungary’s neighbours are also successor states of the Kingdom of Hungary dissolved in 1918, their entangled history, often marred by violence and mutual discrimination was an important and conflictual issue around the change of regime. EU integration efforts led to attempts to implement historical reconciliation following the German model of Vergangenheitsbewältigung and Aufarbeitung and the Franco-German reconciliation. I argue that the result was ambiguous at best. Political tensions abated with all neighbours but without historical reconciliation. One reason for this failure was the division within the historiographic field that made politics easy to instrumentalize or intervene. Tensions receded more because politics started to abandon a historical argumentation in bilateral relations and tha could be a model to follow for states like North Macedonia and Bulgaria. Author(s): Gábor Egry Title (English): Historical Reconciliation: Hungarian Lessons Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 20, No. 1-2 (2023). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 8-19 Page Count: 12 Citation (English): Gábor Egry, "Historical Reconciliation: Hungarian Lessons,” Identities: Journal for Politics, Gender and Culture, Vol. 20, No. 1-2 (2023): 8-19.